2010
DOI: 10.1111/j.1365-2699.2009.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the introduced species Rattus rattus in the western Indian Ocean, with special emphasis on the colonization history of Madagascar

Abstract: Aim To describe the phylogeographic patterns of the black rat, Rattus rattus, from islands in the western Indian Ocean where the species has been introduced (Madagascar and the neighbouring islands of Réunion, Mayotte and Grande Comore), in comparison with the postulated source area (India).Location Western Indian Ocean: India, Arabian Peninsula, East Africa and the islands of Madagascar, Réunion, Grande Comore and Mayotte.Methods Mitochondrial DNA (cytochrome b, tRNA and D-loop, 1762 bp) was sequenced for 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 47 publications
11
126
1
Order By: Relevance
“…This analysis showed that MAYOV clusters within the Thailand hantavirus clade closer to the isolates circulating in the Indian Ocean, South-East Asia (Hugot et al, 2006;Plyusnina et al, 2009;Johansson et al, 2010) and Madagascar (Reynes et al, 2014), rather than the Murinae-associated hantaviruses circulating in continental Africa (Klempa et al, 2006(Klempa et al, , 2012Witkowski et al, 2014). The data suggested that both MAYOV and Anjozorobe virus, the closest variant within the Thailand hantavirus clade, may have resulted from a westward expansion of an ancestral South-East Asian hantavirus introduced with R. rattus (Cheke & Hume, 2008;Tollenaere et al, 2010). Pairwise sequence identities between their coding regions, calculated with the BLASTN tool available online at http://blast.ncbi.nlm.nih.gov/Blast.cgi, were 91/99 % (nucleotide/amino acid identity) for the S segment, 90-91/ 97-98 % (nucleotide/amino acid identity) for the M segment (for ATD49 and AT261 Anjozorobe virus strains, respectively) and 90/99 % (nucleotide/amino acid identity) for the L segment.…”
mentioning
confidence: 96%
“…This analysis showed that MAYOV clusters within the Thailand hantavirus clade closer to the isolates circulating in the Indian Ocean, South-East Asia (Hugot et al, 2006;Plyusnina et al, 2009;Johansson et al, 2010) and Madagascar (Reynes et al, 2014), rather than the Murinae-associated hantaviruses circulating in continental Africa (Klempa et al, 2006(Klempa et al, , 2012Witkowski et al, 2014). The data suggested that both MAYOV and Anjozorobe virus, the closest variant within the Thailand hantavirus clade, may have resulted from a westward expansion of an ancestral South-East Asian hantavirus introduced with R. rattus (Cheke & Hume, 2008;Tollenaere et al, 2010). Pairwise sequence identities between their coding regions, calculated with the BLASTN tool available online at http://blast.ncbi.nlm.nih.gov/Blast.cgi, were 91/99 % (nucleotide/amino acid identity) for the S segment, 90-91/ 97-98 % (nucleotide/amino acid identity) for the M segment (for ATD49 and AT261 Anjozorobe virus strains, respectively) and 90/99 % (nucleotide/amino acid identity) for the L segment.…”
mentioning
confidence: 96%
“…36,37 Tollenaere and others 38 showed that Mayotte presents (at least) three genetic variants of R. rattus that are very similar to Malagasy R. rattus genotypes but different from those of East Africa. Moreover, some Leptospira strains reported in Mayotte have previously been described in East Africa 3,39,40 : This may be indicative of a two-step colonization pattern: Mayotte was first colonized by the East African R. rattus carrying East-African leptospiral strains, but significant migrations from Madagascar occurred later.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
“…The Malagasy black rats could have driven out earlier East African occupants. 38 Consequently, Leptospira species first arrived with the East African R. rattus, and then may have infected introduced Malagasy black rats. The actual strains circulating in Mayotte might result from a genetic selection pressure, a selection by the hosts, and possibly DNA recombination events.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
“…Haplotype 1 has a world-wide distribution, including Antilles, Britain, Europe, French Polynesia, Guadeloupe, Mediterranean Basin, New Guinea, New Zealand, Polynesia, West Africa, and the USA (Robins et al 2007;Nilsson et al 2010;Tollenaere et al 2010;Colangelo et al 2015). It is common in New Zealand, but we did not find it on Stewart Island.…”
Section: Resultsmentioning
confidence: 49%
“…Our analysis is possible due to the availability of rat samples from the island which are both contemporary (just prior to the eradication; Harper & Rutherford 2016) and historical (just after the invasion; Te Papa Museum specimens). Analysis of the hypervariable region of mitochondrial DNA, known as the D-loop, allows a broad-scale assessment of population differences, and matches recent approaches used in studies of the ship rats of Madagascar (Hingston et al 2005;Tollenaere et al 2010). By comparing the D-loop signature of rats from Big South Cape Island with that of rats from surrounding locations, which have previously been hypothesised as potential sources for the invasion (Table 1), we attempt to resolve the question, "where did the rats on Big South Cape Island come from?"…”
Section: Introductionmentioning
confidence: 99%